Pengaruh Intellectual Capital Terhadap Kualitas Laba: - Novita Anggraini; Nurzi Sebrina; Mayar Afriyenti (Universitas Negeri Padang, 2019)
This research aims to examine the effect of intellectual capital of earnings quality. Population in this research are manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2014 to 2017. The sample of study was determined by using purposive sampling method, and that total sample 52 manufacturing companies. The data used is secondary data. The technique of collecting data by documentation at www.idx.com. The analytical method used is Panel Regression Analysis with Eviews8 software. The results showed that the variables of Value Added Capital Employed (VACA) had a significant positive effect on Earning quality. Value Added Human Capital (VAHU) had no effect on Earning quality and Structural Capital Value Added (STVA) had no effect on earning quality